Briefkaarten verstuurd en geschreven aan Nederlandse vrienden door Van het Reve en zijn vrouw vanuit de USSR
Briefkaarten verstuurd en geschreven aan Nederlandse vrienden door Van het Reve en zijn vrouw vanuit de USSR.